FROM MIGRATION ASPIRATIONS TO INTEGRATION: CONTRASTING PIONEER AND RECENT MOLDOVAN MIGRANTS IN ROMANIA - Monica ROMAN; Vlad I. ROȘCA; Elena-Maria PRADA; Ioana MANAFI (Eastern European Journal of Regional Studies, 2023)
Using an exploratory research, this paper aims to gain in depth information on Moldovan migrants in Romania across different generations. It focuses on changes in migrants' aspirations over time and how historical context influences coping strategies. The study compares behavior and experiences of earlier Post-Socialist migrants (pioneer migrants) with recent young migrants in Iasi and Bucharest. Results indicate evolving aspirations and reduced integration barriers, with recent migrants benefiting from technological progress and easier access to Romanian citizenship, facilitating faster integration.